The life of a number : measurement, meaning and the media - Lawson, Brendan (Book collections on Project MUSE., 2023)
Drawing on case studies, this book examines how politicians, academics and journalists gave meaning to data during the COVID-19 pandemic. Lawson sheds light on the distinct nature of the pandemic that led to the increased politicization of data and how it permanently changed the way we view health and society more broadly.